Desenvolvimento de protetor corta luz portátil utilizando materiais têxteis pós-consumo - Hirata, Ewerton (2023)
The generation of post-consumer textile solid waste and its incorrect disposal is a major environmental problem, so the development of new products using these materials is a way to minimize this problem. Thus arises the proposal of the present study with the objective of developing a portable light protector reusing post-consumer textile materials, using the qualitative methodology of an experimental research. Product development is based on the phases of Back et. al. (2008) product development model and has been divided into activities and tasks. This accessory was designed to be attached to the side window of public transport buses, which in addition to life to minimize the environmental impact, contributes to improving the quality of life and comfort of bus users, minimizing the thermal and visual discomfort caused by exposure to the sun's rays. With the development of the portable light protector, it is clear that it is possible to reuse materials, increasing the life cycle of the post-consumer textile materials used, partially efficient in blocking natural light, economically viable and accessible to all economic classes.